Use of HLA-B27 tetramers to identify low-frequency antigen-specific T cells in Chlamydia-triggered reactive arthritis. - Appel, H; Kuon, W; Kuhne, M; Wu, P; Kuhlmann, S; Kollnberger, S; Thiel, A; Bowness, P; Sieper, J (BioMed Central, 2004)
Reports of the use of HLA-B27/peptide tetrameric complexes to study peptide-specific CD8+ T cells in HLA-B27+-related diseases are rare. To establish HLA-B27 tetramers we first compared the function of HLA-B27 tetramers with HLA-A2 tetramers by using viral epitopes. HLA-B27 and HLA-A2 tetramers loaded with immunodominant peptides from Epstein-Barr virus were generated with comparable yields and both molecules detected antigen-specific CD8+ T cells. The application of HLA-B27 tetramers in HLA-B27-related diseases was performed with nine recently described Chlamydia-derived peptides in synovial fluid and peripheral blood, to examine the CD8+ T cell response against Chlamydia trachomatis antigens in nine patients with Chlamydia-triggered reactive arthritis (Ct-ReA). Four of six HLA-B27+ Ct-ReA patients had specific synovial T cell binding to at least one HLA-B27/Chlamydia peptide tetramer. The HLA-B27/Chlamydia peptide 195 tetramer bound to synovial T cells from three of six patients and HLA-B27/Chlamydia peptide 133 tetramer to synovial T cells from two patients. However, the frequency of these cells was low (0.02-0.09%). Moreover, we demonstrate two methods to generate HLA-B27-restricted T cell lines. First, HLA-B27 tetramers and magnetic beads were used to sort antigen-specific CD8+ T cells. Second, Chlamydia-infected dendritic cells were used to stimulate CD8+ T cells ex vivo. Highly pure CD8 T cell lines could be generated ex vivo by magnetic sorting by using HLA-B27 tetramers loaded with an EBV peptide. The frequency of Chlamydia-specific, HLA-B27 tetramer-binding CD8+ T cells could be increased by stimulating CD8+ T cells ex vivo with Chlamydia-infected dendritic cells. We conclude that HLA-B27 tetramers are a useful tool for the detection and expansion of HLA-B27-restricted CD8+ T cells. T cells specific for one or more of three Chlamydia-derived peptides were found at low frequency in synovial fluid from HLA-B27+ patients with Ct-ReA. These cells can be expanded ex vivo, suggesting that they are immunologically functional.